2‐Nitrobenzyl Isocyanide as a Universal Convertible Isocyanide. Issue 7 (18th May 2017) - Chandgude, Ajay L.; Li, Jingyao; Dömling, Alexander
Abstract: 2‐Nitrobenzyl isocyanide is reported as a universal convertible isocyanide with extensive applicability in both Ugi four‐component reaction (Ugi‐4CR) and Ugi‐tetrazole reaction. The cleavage of this isocyanide from 17 examples in both acidic and basic conditions is presented. Additionally, this isocyanide has various handling and synthetic advantages, as it is easy to prepare, odorless, stable, and easy to handle as a solid. Abstract : Cruising in a convertible : 2‐Nitrobenzyl isocyanide is reported as a universal convertible isocyanide with extensive applicability in both Ugi‐4CR and Ugi‐tetrazole reactions. The cleavage of this isocyanide from 17 examples in both acidic and basic conditions is presented.